A Fundamental Instability for the Solar Wind - Kellogg, Paul J. (The Astrophysical journal, 2022)
As has been known nearly since the beginning of space research with satellites and rockets that the temperature of the atmosphere of our Sun rises rapidly from the photosphere at about 6000 K to the order of 10 6 K. The major heating of the solar wind apparently occurs in a narrow region, the transition region, just above the chromosphere, a region where remote sensing of atomic energy levels shows a temperature of 10 6 deg. However, since the early days of the recognition of the solar wind it has been recognized that there must also be further heating as the solar wind escapes the Sun, to overcome adiabatic cooling, and it is this heating that is the subject of the Parker Solar Probe mission, and of this work. As is well known, the solar wind is turbulent, which suggests that plasma instabilities play an important role in its behavior. The role of instabilities in shaping the solar wind was clearly shown by Kasper et al. and Hellinger et al. As shown in Figure 4 of Kasper or Figure 1 of Hellinger, the distribution function of the ions is limited by well-known instabilities. It seems that there ought to be an instability that is common and depends on omnipresent plasma characteristics. In this work it is assumed that such may be provided by the expansion of the solar wind magnetic field as it leaves the Sun.